Micronutrients Intake Status Between Risk and Non-Risk Anemia Groups Among University Students in Indonesia - Desi Nurmilah; Arif Sabta Aji; Siti Helmyati; Esti Nurwanti (Ikatan Sarjana Gizi Indonesia (ISAGI), 2021)
Anemia status is one of the public health problems at both global and Indonesia. The prevalence of anemia was found higher in the women of reproductive age. The prevalence in Special Region of Yogyakarta was even larger than the national average (34% vs 21.7%) for women of reproductive age group. Poor intake of micronutrient could be a major contributor to anemia. The aim of this study was to determine the difference of micronutrient intake among student with risk and no-risk anemia in the Alma Ata University. This cross-sectional study conducted from August to September 2020. Of 128 subjects was recruited and divided into two groups (64 risk anemia and 64 non-risk anemia group). The screening of anemia status was obtained by using self-assessment of clinical/physical questionnaires. Micronutrient intakes such as iron, folic acid, zinc, vitamin B6 and B12, cooper, and vitamin C were assessed by Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). Independent T-test was created to analyze the difference of micronutrient intake in risk and non-risk anemia groups. In this study, there were significant differences in the intake of micronutrients such as iron (p <0.001), folic acid (p <0.001), Zn (p <0.001), vitamin B6 (p <0.001), B12 (p = 0.008), and vitamin C (p <0.001) among students in risk and non-risk of anemia. However, there was no significant difference in Cu intake (p = 0.975). In conclusion, lower micronutrient intake among students could lead to have higher anemia risk. Further studies with larger samples are required to confirm these findings.